Implementasi Hak Pekerja Alih Daya di Perusahaan Penyedia Jasa Pengamanan - Permatasari, Eka Yuni; Phahlevy, Rifqi Ridlo (Indonesian Journal Publisher, 2024)
The work culture in a business entity that is currently happening is certainly inseparable from the existece of a work agreement. Where the work agreement will bind both parties to carry out their respective obligations. One of which is related to the existence of Outsourced Workers Rights in a company that operates in the field of Security Service, to uphold the rights of every worker, this paper aims to find out the Implementation of the rights of outsources worker, as well as what the efforts are made by workers to fight for their rights. This studyuses an empirical juridical method that examines normative application with in action on every legal phenomenon that occurs in the society, so this study shows that the implementation of the welfare of outsources workers which includes wages, guarantees, working time, ets. Can not be carried out optimally, this because of some social security of workers in some compaines are not fully provided.